Salmonella Virchow Infection of the Chicken Elicits Cellular and Humoral Systemic and Mucosal Responses, but Limited Protection to Homologous or Heterologous Re-Challenge - Salisbury, Anne-Marie; Leeming, Gail; Nikolaou, Georgios; Kipar, Anja; Wigley, Paul (Frontiers in Veterinary Science, 2014)
Salmonella enterica serovar Virchow usually causes mild gastroenteritis in humans; however, it is frequently invasive and many isolates are resistant to a broad range of therapeutic antimicrobials. Poultry meat is considered a major source of human infection. In this study, we characterise the infection biology and immune response to S. Virchow in chickens and determine protection against homologous and heterologous re-challenge, with S. Virchow or S. Typhimurium. Following oral infection of 7-day-old chickens, S. Virchow colonised the gastrointestinal tract and the spleen. Infection elicited an increase in specific IgA, IgG and IgM antibodies and relative quantitative changes in several leukocyte populations, including CD3, CD4, CD8α, CD8β, MHC II, KuL01 and γδ TCR positive cells, both in the gastrointestinal tract and systemically. Increased expression of pro-inflammatory cytokines IL-1β and IL-6 and the chemokine CXCLi2 was also found. Primary infection with S. Virchow offered limited systemic protection against re-challenge with S. Virchow or S. Typhimurium, but no protection against caecal colonisation. In conclusion, S. Virchow exhibits similar infection biology and immune responses in the chicken to that previously described for S. Typhimurium. Unlike S. Typhimurium, S. Virchow infection is poorly protective to homologous and heterologous re-challenge. These findings suggest that S. Virchow is capable of colonising the chicken well and therefore, presents a risk of entering the food chain in meat production. Furthermore, the development of vaccines that protect effectively against S. Virchow and indeed multivalent vaccines that protect across all Salmonella serogroups in the chicken would appear to remain a challenging proposition.